Enhancing Sharia Microbusinesses: The Implementation of Microfinance Institution Regulations at the Micro Waqf Bank Sumber Barokah - Dianitasari, Putri; Asari, Aang; Pangestu, Satrio Anugrah (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2023)
Abstract: Frequently, individuals involved in productive endeavors encounter difficulty in securing business capital. In response to this issue, government has initiated national program including the implementation of Microfinance Institutions (MFIs), aimed at providing capital to Micro, Small, and Medium Enterprises (UMKM). Within this framework, the emergence of the Micro Waqf Bank (BWM) served as a solution to empower productive underprivileged communities. The research aims to investigate the efficacy of BWM in fostering the development of micro-enterprises within the vicinity of Islamic boarding schools (pesantren). A qualitative approach was adopted for this research, employing methodologies involving observation, interviews, and documentation to gather research data. The finding of this study reveals that the financial distribution mechanisms of the BWM Sumber Barokah Denanyar comply with prevailing legislative regulations, utilizing qardh contracts aligned with Sharia principles. Furthermore, the financing provided by the Micro Waqf Bank significantly contributes to the advancement of business activities among productive underprivileged communities. Operationally, the BWM Sumber Barokah Denanyar adheres to the guidelines stipulated in Law No. 1 of 2013 concerning Microfinance Institutions. Moreover, in addition to fostering the nation's economy, the Micro Waqf Bank plays a pivotal role by providing financial resources to uplift productive underprivileged communities in Indonesia.Abstrak: Biasanya, individu yang terlibat dalam usaha produktif mengalami kesulitan dalam mendapatkan modal usaha. Sebagai tanggapan terhadap masalah ini, pemerintah telah menginisiasi program nasional, termasuk implementasi Lembaga Keuangan Mikro (LKM), yang bertujuan untuk menyediakan modal bagi Usaha Mikro, Kecil, dan Menengah (UMKM). Dalam kerangka ini, munculnya Bank Wakaf Mikro (BWM) berperan sebagai solusi untuk memberdayakan masyarakat kurang mampu secara produktif. Penelitian ini bertujuan untuk menyelidiki efektivitas BWM dalam mendorong perkembangan usaha mikro di sekitar pesantren. Pendekatan kualitatif digunakan untuk penelitian ini, dengan mengadopsi metodologi observasi, wawancara, dan dokumentasi untuk mengumpulkan data penelitian. Hasil dari penelitian ini mengungkapkan bahwa mekanisme distribusi keuangan dari BWM Sumber Barokah Denanyar sesuai dengan regulasi legislasi yang berlaku, menggunakan kontrak qardh yang sesuai dengan prinsip syariah. Selain itu, pembiayaan yang diberikan oleh Bank Wakaf Mikro secara signifikan berkontribusi pada kemajuan kegiatan usaha di kalangan masyarakat kurang mampu secara produktif. Secara operasional, BWM Sumber Barokah Denanyar mematuhi pedoman yang diatur dalam Undang-Undang No. 1 tahun 2013 tentang Lembaga Keuangan Mikro. Selain memajukan ekonomi bangsa, Bank Wakaf Mikro juga memainkan peran penting dengan menyediakan sumber daya keuangan untuk meningkatkan masyarakat kurang mampu secara produktif di Indonesia.